Measuring Beta Capm In 2 Economic Stages Of Commercial Banks In Vietnam Economy – Case Of Vietcombank And Vietinbank - TRUNG, NGUYEN DINH; HUY, DINH TRAN NGOC; THUY, NGUYEN THU; NUONG, LE NGOC; HAC, LE DINH (The journal of contemporary issues in business and government, 2021)
Vietcombank (VCB) and Vietinbank (CTG) are two big listed commercial banks in Vietnam banking industry. They are previous state-owned enterprises with big market share in local market. This paper will use statistic, combined with synthesis, inductive and qualitative analysis to measure and evaluate beta CAPM of these 2 banks in2 special stages of domestic economy: pre-L and post-low (L) inflation time. Research results show that during 2011-2020 period, most of time, beta CAPM of VCB is higher than those of CTG bank. Statistic chart give us warning that market risk of 2 banks is higher than 1. Then these analysis can be used for policy implications. Business and banking is still growing so risk management is becoming meaningful for the financial industry.